Why Do Chinese Employees Complain at the Workplace? An Exploratory Study Based on the Theory of Work Adjustment - Yuan, Shaofeng; Gao, Ying (Frontiers in Psychology, 2022)
This study aims to investigate the causes of workplace complaints among Chinese employees and to develop a scale to measure them, drawing on the theory of work adjustment. We first obtained 49 items regarding employees’ complaints following rigorous item generation and refinement procedures. Then, we conducted a survey with convenience sampling and obtained a sample of 268 employees. The exploratory factor analysis based on this sample generated a six-factor solution that explained 65.85% of the variance. The six factors include four person-environment (P-E) interactional factors, namely, dissatisfaction with: (a) interpersonal relationships; (b) management systems; (c) work conditions; and (d) authoritarian leadership; and two P-E misfit factors, namely, perceived misfit regarding: (e) work content; and (f) job responsibilities. Furthermore, we obtained another sample of 349 employees through snowball sampling, on which we further validated the six-correlated-factor solution through confirmatory factor analysis. This study contributes to the literature by identifying causes of Chinese employees’ complaints different from those attributed to their counterparts in Western cultures. This outcome particularly reveals that “dissatisfaction with interpersonal relationships” with colleagues was the leading cause of complaints among Chinese employees, rather than the “misfit between employees’ needs and organizational rewards” revealed by Western culture-based studies. Both our findings and the scale we developed have practical implications for companies that employ Chinese employees.